2017
DOI: 10.1111/gbb.12383
|View full text |Cite
|
Sign up to set email alerts
|

The role of NMDA receptor‐dependent activity of noradrenergic neurons in attention, impulsivity and exploratory behaviors

Abstract: Activity of the brain's noradrenergic (NA) neurons plays a major role in cognitive processes, including the ability to adapt behavior to changing environmental circumstances. Here, we used the NR1 DbhCre transgenic mouse strain to test how NMDA receptor-dependent activity of NA neurons influenced performance in tasks requiring sustained attention, attentional shifting and a trade-off between exploration and exploitation. We found that the loss of NMDA receptors caused irregularity in activity of NA cells in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…We previously found that NA release in the auditory midbrain of S. bombifrons differed in response to conspecific (S. bombifrons) and heterospecific (S. multiplicata) mating calls (Burmeister et al, 2017), suggesting that a role for NA in auditory processing of social signals may be conserved. Interestingly, levels of NA in the preoptic area of S. bombifrons, in contrast, were modified by diet in a manner that mirrored adult social preferences (Burmeister et al, 2017), an effect that is broadly consistent with a role for NA in behavioural flexibility and motivation (Jahn et al, 2018;Lapiz and Morilak, 2006;Cie slak et al, 2017).…”
Section: Introductionmentioning
confidence: 55%
“…We previously found that NA release in the auditory midbrain of S. bombifrons differed in response to conspecific (S. bombifrons) and heterospecific (S. multiplicata) mating calls (Burmeister et al, 2017), suggesting that a role for NA in auditory processing of social signals may be conserved. Interestingly, levels of NA in the preoptic area of S. bombifrons, in contrast, were modified by diet in a manner that mirrored adult social preferences (Burmeister et al, 2017), an effect that is broadly consistent with a role for NA in behavioural flexibility and motivation (Jahn et al, 2018;Lapiz and Morilak, 2006;Cie slak et al, 2017).…”
Section: Introductionmentioning
confidence: 55%
“…One study tested how NMDA receptor dependent activity of NA neurons in performance of sustained attention and showed the loss of NMDA receptors associated with decreased sustained attention cognitively and increased impulsivity at the level of behavior. 37 Sustained attention deficits are frequently reported in psychiatric and physical conditions. Esterman et al 38 reported that failure of inhibition on the sustained attention test was higher in patients with PTSD and substance use disorder.…”
Section: Discussionmentioning
confidence: 99%
“…The Go/no-go test was performed based on protocols previously used by us (Cieslak et al , 2017). Details of the procedure can be found in the Supplemental Methods.…”
Section: Methodsmentioning
confidence: 99%